2002
DOI: 10.1177/105268460201200502
|View full text |Cite
|
Sign up to set email alerts
|

School Leadership Reforms: Filtering Social Justice through Dominant Discourses

Abstract: Do administrative licensure policy reforms address social justice concerns? By analyzing the policy discourse (in interviews and documents) in Indiana and North Carolina, this article shows that policy actors believe the focus on heightened standards will raise the quality of leadership candidates. In turn, they believe that this focus on quality will address diversity, achievement gaps, and other equity issues. However, they are concerned about whether higher education can and will adequately implement the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Marshall and McCarthy (2002) found that in two states, particular state definitions of social justice and state priorities refined, focused, and indeed were filters through which policy makers were shaping leadership training and licensure policy. Two North Carolina policy makers said, "We have no idea how to assess things like caring, social justice, inclusion" and "The state spends big money on professional development but it's broken and we have to find ways to fix it."…”
mentioning
confidence: 98%
“…Marshall and McCarthy (2002) found that in two states, particular state definitions of social justice and state priorities refined, focused, and indeed were filters through which policy makers were shaping leadership training and licensure policy. Two North Carolina policy makers said, "We have no idea how to assess things like caring, social justice, inclusion" and "The state spends big money on professional development but it's broken and we have to find ways to fix it."…”
mentioning
confidence: 98%
“…Indeed, the tangible outcomes of accountability policies grossly disregard the challenges of equity and race, class and gender. It promotes an ideological hegemonic frame and, consequently, assumes that accountability through testing and assessments promotes the nation's prosperity and serves the needs of the underrepresented (Marshall and McCarthy 2002). Therefore, my students, transformed as researchers, had to identify very creative strategies to seek permission by their school principals to undertake their research projects in the classrooms.…”
Section: The Methods For the 'Shift': Participatory Action Researchmentioning
confidence: 99%
“…Foucault (1979) describes this idea as ''the normalizing gaze'' and its significance is that ''it appears to be neutral'' (Usher & Edwards, 1996, p. 103). This is extremely difficult to do 32 FENWICK W. ENGLISH when the knowledge base is actually ambiguous, multi-dimensional, highly subjective, non-empirical and filled with huge epistemological holes (see Anderson, 2001;Dantley & Rogers, 2001;English, 2000aEnglish, , 2002aFurman & English, 2002;Littrell & Foster, 1995;Marshall & McCarthy, 2002). To engage in actions which may potentially disbar preparation programs from continuing, the knowledge base on the which the ELCC standards rest has to be portrayed as: (a) unequivocal and unidimensional; (b) possess the veneer of objectivity and scientificity; (c) be supported by forms of political consensus which minimize the dissent which will emerge when policing actions result in disbarment.…”
Section: Problems With the Knowledge Base: Producing An Unequivocal Pmentioning
confidence: 99%